The architecture of transcendence: John Webster and Dietrich Bonhoeffer on divine agency, Christology and theological method - Clark-Howard, Andrew (Scottish journal of theology, 2023)
John Webster and Dietrich Bonhoeffer are two theologians invested in prioritising certain conceptions of divine transcendence within their respective theological projects. Specifically, both appeal to conceptions of divine transcendence and agency amidst what they understand to be the problematic naturalisation of theological discourse in modern Protestant theology, particularly within its liberal German traditions. The way they understand transcendence, however, and the doctrinal loci they choose to affect it, leads to different conceptualisations of the possibilities, scope and organisation of systematic theology. Where Webster (especially in his later work) seeks to prioritise God's immanent perfection and aseity through theology proper, Bonhoeffer instead emphasises God's freedom pro me within the person of Jesus Christ. These differences in first theological foundations have important consequences for the shape of theological method and doctrinal architecture within the practice of contemporary systematic theology.